Decision support in clinical dentistry - Jonathan Rudin (Universidade Estadual de Campinas, 2015)
A comprehensive method for retrieving information to address dental patients' problems is outlined. The desired outcome is to have fully informed patients receive optimal treatment. The first step is to create a research question that can be effectively used as the basis for a computerized search. Next, a suitable information resource is selected for searching. Reasons for regarding controlled clinical trials as the foundation for evidence-based decision support are presented. A search strategy using keywords and other constraints is then created. Complexities associated with keyword searches are described. Next, the retrieved citations are assessed for relevance. Irrelevant citations are eliminated and the remaining ones interpreted. The concepts of statistical and practical significance are presented. Next, knowledge from the retrieved citations is combined with patient-specific information. After completing this step, patients can be properly informed about their choices and treated accordingly.